Housing Movements and Participation in Institutional Spaces (Alternautas, 2022)
This article sets out to examine the inclusion of social movements in the designing of public policy in Brazil. I situate the Brazilian political and social context in terms of its persistent social inequalities and the inclusion of social movements in policy-making during the course of 2003–2010 (Lula da Silva’s first and second terms as president) and 2011–2014 (Dilma Rousseff’s first term as president). I discuss and explore mechanisms of participatory democracy, and more specifically, I look at the process of integration of civil society in spaces of decision-making related to housing issues. This paper found that, despite some concrete results of implementing greater popular participation, the inclusion of social movements still faces challenges to be effectively included in spaces of decision-making, especially under the current conservative administration.